Geschiedenis van de seksuele normen : oudheid, middeleeuwen, 17de eeuw - van Emde Boas, Coen (Antwerpen : De Nederlandsche Boekhandel, 1985)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie
Keywords: seksualiteit